Examination of Salivary Cortisol as a Biomonitoring of Work-Related Stress - Muhammad Reza Aditya; Muhammad Ilyas (The Indonesian Journal of Occupational Safety and Health, 2022)
Introduction: Stress is a condition that must bepaid attention to by workers and employers, 87% of the workers from Europe claimed that they suffered from stress in the workplace. In 2015 around 28% of the workers reported suffering from work-related stress, with 33% clinical manifestations of fatigue, 19% sleep disturbances and 18% anxiety. Impacts that can affect workers can be absenteeism, presenteeism, etc. This study aims to investigate salivary cortisol examination to examine work-related stress using the evidence-based case report method. Methods: A literature review was conducted on November 23, 2020 through searches on the PubMed, Cochrane, and Google Scholar databases to find all published observational studies evaluating the relationship between salivary cortisol and work-related stress. Results: After screening using inclusion criteria and reducing the duplication of articles, 5 articles were obtained. Conclusion: it can be concluded that the salivary cortisol test tool can be used as an additional objective examination in order to check stress conditions in workers, in addition to a subjective examination like a questionnaire or anamnesis on workers. It is used for a biomonitoring effect and susceptibility biomonitoring. This salivary cortisol test can also be used to help determine stress levels in workers in order to detect early occupational diseases associated with psychosocial hazards.Keywords: biomonitoring, salivary cortisol, work-related stress